The effectiveness of traditional vs. velocity-based strength training on explosive and maximal strength performance: A network meta-analysis - Held, Steffen; Speer, Kevin; Rappelt, Ludwig; Wicker, Pamela; Donath, Lars (Frontiers in Physiology, 2022)
This network meta-analysis aimed at evaluating the effectiveness of different velocity-based (VBT) and traditional 1RM-based resistance training (TRT) interventions on strength and power indices in healthy participants. The research was conducted until December 2021 using the online electronic databases PubMed, Web of Science, PsycNet, and SPORTDiscus for studies with the following inclusion criteria: (a) controlled VBT trials, (b) strength and/or jump and/or sprint parameters as outcomes (c), participants aged between 18 and 40 years, and (d) peer-reviewed and published in English. Standardized mean differences (SMD) using a random effects models were calculated. Fourteen studies with 311 healthy participants were selected and 3 networks (strength, jump, and sprint) were achieved. VBT, TRT, repetitions in reserve (RIR), low velocity loss (lowVL), and high velocity loss (highVL) were ranked for each network. Based on P-score rankings, lowVL (P-score ≥0.59; SMD ≥0.33) and highVL (P-score ≥ 0.50; SMD ≥0.12) revealed favorable effects on strength, jump, and sprint performance compared to VBT (P-score ≤ 0.47; SMD ≤0.01), TRT (P-score ≤0.46; SMD ≤0.00), and RIR (P-score ≤ 0.46; SMD ≤0.12). In conclusion, lowVL and highVL showed notable effects on strength, jump, and sprint performance. In particular for jump performance, lowVL induced favorable improvements compared to all other resistance training approaches.